Calcium‐signaling components in rat insulinoma β‐cells (INS‐1) and pancreatic islets are differentially influenced by melatonin. Issue 4 (9th April 2014) - Bazwinsky‐Wutschke, Ivonne; Mühlbauer, Eckhard; Albrecht, Elke; Peschke, Elmar
Abstract The pineal secretory product melatonin exerts its influence on the insulin secretion of pancreatic islets by different signaling pathways. The purpose of this study was to analyze the impact of melatonin on calcium‐signaling components under different conditions. In a transfected INS‐1 cell line overexpressing the human MT2 receptor (hMT2‐INS‐1), melatonin treatment induced even stronger depressive effects on calcium/calmodulin‐dependent kinase 2d and IV (Camk2d, CamkIV) transcripts during 3‐isobutyl‐1‐methylxanthine (IBMX) treatment than in normal INS‐1 cells, indicating a crucial influence of melatonin receptor density on transcript‐level regulation. In addition, melatonin induced a significant downregulation of calmodulin (Calm1) in IBMX‐treated hMT2‐INS‐1 cells. Long‐term administration of melatonin alone reduced CamkIV transcript levels in INS‐1 cells; however, transcript levels of Camk2d remained unchanged. The release of insulin was diminished under long‐term melatonin treatment. The impact of melatonin also involved reductions in CAMK2D protein during IBMX or forskolin treatments in INS‐1 cells, as measured by an enzyme‐linked immunosorbent assay, indicating a functional significance of transcriptional changes in pancreatic islets. Furthermore, analysis of melatonin receptor knockout mice showed that the transcript levels of Camk2d, CamkIV, and Calm1 were differentially influenced according to the melatonin receptor subtype deleted. In conclusion, this study provides evidence that melatonin has different impacts on the regulation of Calm1 and Camk. These calcium‐signaling components are known as participants in the calcium/calmodulin pathway, which plays an important functional role in the modulation of the β‐cell signaling pathways leading to insulin secretion.